Influence of Low Temperatures on Laser- Induced Breakdown Spectroscopy of Silicon Rubber Insulators - Tian, Liang; He, Yongqi; Deng, Yu; Liu, Zheyuan; Wang, Qi; Wang, Xilin (IEEE transactions on dielectrics and electrical insulation, 2024)
Silicon rubber composite insulators are extensively utilized in high-voltage power transmission and transformation equipment owing to their excellent hydrophobicity characteristics and strong resistance to pollution flashover. However, with prolonged operation times, composite insulators undergo varying degrees of aging, compromising the safe operation of power transmission lines. Efficient and accurate in situ detection methods for composite insulators are currently lacking. Laser-induced breakdown spectroscopy (LIBS) technology is advantageous owing to its long-distance detection capability, simplicity, and quickness, making it suitable for assessing the aging status of silicon rubber. China's ultrahigh-voltage (UHV) power lines cover a wide area ranging from the frigid zone of Heilongjiang in the north to the tropical region of Yunnan in the south. These operating environments are highly complex and are prone to significant temperature variations that may interfere with the laser spectral data. Therefore, this study primarily investigates the influence patterns and mechanisms of low temperatures on LIBS and proposes corresponding detection strategies. The results demonstrate that within the temperature range of −35 °C to −25 °C, when the sample temperature drops below 0 °C, the ice crystal layer formed by the condensation of water vapor on the sample surface consumes a portion of the laser energy, leading to a noticeable reduction in the spectral line intensity, electron density, and plasma temperature. This study contributes to mitigating the interference of low temperatures on laser spectral data and enhancing the precision of the LIBS quantitative analysis, making it possible to apply LIBS to power transmission line inspections to ensure the safe and stable operation of these lines.